Problem-Based Learning Media: " Tepuk Kartu (Tukar)" for Teaching Addition and Subtraction in Grade II Elementary School Mathematics - Ni Kadek Kerlina Pradnya Pratiwi; Anak Agung Gede Agung; I Wayan Wiarta (Mimbar Pendidikan Indonesia, 2025)
The lack of innovative, contextual, and student-centered instructional media in early-grade classrooms contributes to low student engagement and poor academic performance in Mathematics learning. This condition calls for a solution through the integration of play-based, contextual, and problem-solving learning media. This study aims to develop, validate, and evaluate the effectiveness of a problem-based instructional media called “Tukar (Tepuk Kartu)” to enhance students' Mathematics learning outcomes. The research employed a research and development (R&D) design using the ADDIE model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects included four expert validators (media design, content, instructional design, and construction) and 27 second-grade elementary school students. Data were collected through expert validation questionnaires, student response surveys, and multiple-choice tests. The data were analyzed using descriptive quantitative methods and a one-sample t-test. Expert validation results indicated the media was “highly feasible” with average scores above 80%. The effectiveness test revealed that the tvalue (2.341) exceeded the critical value (2.056), indicating a significant improvement in student learning outcomes. In conclusion, the “Tepuk Kartu” media is feasible and effective as a contextual, game-based learning tool. This implies that teachers can adopt traditional games as engaging instructional media.